Effect of Integrated Nutrient Management Approach on Growth, Yield, and Economics of Cauliflower (Brassica oleracea L. var botrytis) - Gyanwali, Prakash; Singh, Kanhaiya Prasad; Pathak, Rukmagat; Bhattarai, Bishnu Prasad (Nepalese Horticulture, 2022)
The integrated nutrient management approach addresses the issues arising from the irrational use of chemical fertilizers such as soil quality degradation, and the unsustainability of productivity and profitability. In this study, we evaluated the effect of the integrated nutrient management approach on the growth, yield, and economics of cauliflower (Brassica oleracea L. var botrytis cv. Khumal Jyapu), through a field experiment in Randomized Complete Block Design with three replications and seven treatments- 50% NPK + 6.90 Mt ha-1 vermicompost, 75% NPK + 3.45 Mt ha-1 vermicompost, 50% NPK + 3.75 Mt ha-1 poultry manure, 75% NPK + 1.88 Mt ha-1 poultry manure, 50% NPK + 20.80 Mt ha-1 farmyard manure, 75% NPK + 10.40 Mt ha-1 farmyard manure and 100% recommended NPK, 200:120:80 kg NPK ha-1 as the control. Among the tested treatments, organic and inorganic nutrient sources, in combination, recorded a significant influence on growth and yield-attributing characters as compared to sole inorganic treatment. 50% NPK + 6.9 Mt ha-1 vermicompost recorded highest height (63.33 cm), earliest harvest (73.67 days), largest curd diameter (16.83 cm), highest curd weight (680.53 g), biomass (1384.79 g), curd yield (25.2 Mt ha-1), gross margin (NRs.10,08,000 ha-1), net return (NRs. 6,91,944 ha-1) and B:C ratio (3.19). Desirable growth parameters, higher yield, cost-effectiveness, and profitability from 50% NPK + 6.90 Mt ha-1 vermicompost show that the use of vermicompost is economically viable. Results also show that farmers can reduce chemical fertilizer costs by up to 50% using vermicompost without affecting profitability.